Kontestasi Aktor dalam Proses Revisi Rencana Tata Ruang Provinsi (RTRWP) di Indonesia (Studi Kasus: Revisi RTRW Provinsi Riau) - Suprapto Suprapto; San Afri Awang; Ahmad Maryudi; Wahyu Wardhana (Department of Urban and Regional Planning, Diponegoro University, 2018)
Riau Province is one of the provinces which have not revised the RTRWP until 2017. One possible cause relates to the conflicts of interest among the participating actors. Each actor exercises the power influences to secure individual interests. This study aims to identify the participating actors, to measure the power influences exchanged between the actors and to recommend solutions for resolving the Riau’s RTRWP revision issue. The method used is Actor-Centered Power (ACP) approach, which is supported by Content Analysis of Riau's RTRWP document and related regulations. The research findings show that there are at least nine actors involved in the revision process of the Riau’s RTRWP, where the role of the Ministry of Environment and Forestry is the most powerful then followed by the Riau Province Government. The research also shows the involvement of Ombudsman Agency, private corporations, and non-governmental organization (NGO) in the Riau’s RTRWP revision process. To accelerate the completion of the Riau’s RTRWP Regional Regulation Draft, coordination and integration between the participating actors are required as well as the law enforcement against legal violations and comprehensive conflict management.